Carbon capture and storage (CCS): the way forward - Bui, Mai; Adjiman, Claire S.; Bardow, André; Anthony, Edward J.; Boston, Andy; Brown, Solomon; Fennell, Paul S.; Fuss, Sabine; Galindo, Amparo; Hackett, Leigh A.; Hallett, Jason P.; Herzog, Howard J.; et al. (Royal Society of Chemistry, 2018)
Carbon capture and storage (CCS) is broadly recognised as having the potential to play a key role in meeting climate change targets, delivering low carbon power, decarbonising industry and, more recently, its ability to facilitate the net removal of CO2 from the atmosphere. However, despite this broad consensus and technical maturity, CCS has not yet been deployed on a scale commensurate with the ambitions articulated a decade ago. Thus, in this paper we review the current state-of-the-art of CO2 capture, transport, utilisation and storage from a multi-scale perspective, moving from the global to molecular scales. In light of the COP21 commitments to limit warming to less than 2 C, we extend the remit of this study to include the key negative emissions technologies (NETs) of bioenergy with CCS (BECCS), and direct air capture (DAC). Cognisant of the non-technical barriers to deploying CCS, we capitalise on recent experience from the UK’s CCS commercialisation programme and consider the commercial and political barriers to the largescale deployment of CCS. In all areas, we focus on identifying and clearly articulating the key research challenges that could usefully be addressed in the coming decade.